Outcomes of dietary management approaches in active ulcerative colitis: A systematic review. Issue 2 (February 2022) - Marsh, Abigail; Rindfleish, Sophie; Bennett, Kalina; Croft, Anthony; Chachay, Veronique
Summary: Background & aims: The dietary management of active ulcerative colitis (UC) is currently poorly understood. Due to the lack of clinical guidelines for this population, diet choice may be based on the personal judgement of the clinician, and without sound evidence. The aim of this systematic review was to appraise the current literature on the dietary management of individuals with active UC, in both inpatient and outpatient settings, to determine if clinical outcomes differ by diet prescription. Method: PUBMED, CINAHL, EMBASE, Web of Science and SCOPUS were comprehensively searched during March and April 2020. Eligible trials recruited adults with active UC comparing different methods of dietary management, including enteral nutrition (EN), total parenteral nutrition (TPN), elimination diets and standard oral diets, in both the inpatient and outpatient settings. Results: 10 studies met inclusion criteria of this qualitative synthesis. No difference was found between EN, TPN and bowel rest in terms of disease activity measures when compared to a standard oral diet. The results of this study also showed promising potential for the use of elimination diets in the outpatient setting with four studies finding a significant difference in disease activity measures between the intervention diet and control. Conclusion: There is no strong evidence to support the use of any specific dietary prescription to improve clinical outcomes for individuals with active UC. A number of low quality studies suggest benefit of following an elimination diet, however, additional high quality studies are required before any more specific recommendations can be made.